Bipolar filipino value of hiya impact on freshmen students use of the Main Library - Alvarez, Frances D.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
It is part of college life that students go to the Library for academic endeavors. t should not be a stressful affair but some students, particularly freshmen undergo some feelings of uneasiness when going to the Library. It has been observed that some of them appear not to know library procedures and seem to be at a loss when doing research work therein. Apart from library anxiety being the possible cause of this behavior, there is a national cultural phenomenon that could be inhibiting those students from asking library staff present about their research issues.This paper studies the influence of the Filipino value of hiya on UPD freshmen's use of the UPML.
The study conducted a descriptive method of research employing a 3-page 28-item written questionnaire to measure the extent of how the value of hiya affects the students' behavior in using the Library. Some 390 questionnaires were distributed among freshmen. Only 366 were returned from where data were extracted then fed to an SPSSver.16 software. Information generated showed that the respondents possess a fair amount of hiya. It also showed that the lesser the frequency of library use, the higher the level of hiya attitude among respondents.
Since hiya is an intrinsic characteristic of a person developed or learned thru the years, it is not easy to address it. It would need creative methods to mitigate the negative aspects and to enhance the positive ones. One suggestion was to make the library tour or orientation mandatory for all freshmen.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library -- Use studies; University of the Philippines (Diliman) -- Freshmen; Library users -- Psychology